Differences in Weight-Related Behavioral Profiles by Sexual Orientation Among College Men: A Latent Class Analysis - VanKim, Nicole A. (Am J Health Promot, 2016)
PURPOSE: To identify and describe homogenous classes of male college students based on their weight-related behaviors (e.g., eating habits, physical activity, and unhealthy weight control) and to examine differences by sexual orientation. DESIGN: Study design was a cross-sectional sample of 2- and 4-year college students. SETTING: Study setting was forty-six 2- and 4-year colleges in Minnesota. SUBJECTS: Study subjects comprised 10,406 college males. MEASURES: Measures were five categories of sexual orientation derived from self-reported sexual identity and behavior (heterosexual, discordant heterosexual [identifies as heterosexual and engages in same-sex sexual behavior], gay, bisexual, and unsure) and nine weight-related behaviors (including measures for eating habits, physical activity, and unhealthy weight control). ANALYSIS: Latent class models were fit for each of the five sexual orientation groups, using the nine weight-related behaviors. RESULTS: Overall, four classes were identified: “healthier eating habits” (prevalence range, 39.4%–77.3%), “moderate eating habits” (12.0%–30.2%), “unhealthy weight control” (2.6%–30.4%), and “healthier eating habits, more physically active” (35.8%). Heterosexual males exhibited all four patterns, gay and unsure males exhibited four patterns that included variations on the overall classes identified, discordant heterosexual males exhibited two patterns (“healthier eating habits” and “unhealthy weight control”), and bisexual males exhibited three patterns (“healthier eating habits,” “moderate eating habits,” and “unhealthy weight control”). CONCLUSION: Findings highlight the need for multibehavioral interventions for discordant heterosexual, gay, bisexual, and unsure college males, particularly around encouraging physical activity and reducing unhealthy weight control behaviors.